Modos de patrimonializar: Nice, estrigas e a dimensão afetiva no Minimuseu Firmeza - Cavalcante, Luiza Helena Amorim Coelho (2023)
The Minimuseu Firmeza was founded in 1969, by the Ceará couple of artists Nice and Estrigas, in the place where they lived, in the Mondubim neighborhood, Fortaleza´s outskirts, serving a political project by positioning itself in the geopolitical defense of a History of Art from Ceará, in defense of artists and art. An equally poetic gesture, of creating a house-museum and continuing to inhabit it, making objects and everyday life heritage, diluting barriers between the public and the private. A collection that includes works of art, the house, the garden and the backyard and a huge baobab tree. In this project, they mobilized various agents from the art world who, in a collaborative way, helped to form the collection and began to develop activities in the space that was marked by the production of knowledge and exchanges. The Minimuseu was based on networks of solidarity, mutual respect, among other characteristics that bring it closer to the Guarani indigenous experience of Teko Porã, translated into Portuguese as bem viver. An experience that can be understood as an “experimental museology” or “indisciplinary museology” given the peculiarities of the museum and, therefore, the difficulty of fitting it into academic categories. The research brings together several fields of knowledge, such as Heritage, Art History in Ceará, Museology, the agencies of Nice and Estrigas in the museological and heritage operational chain, as from their personalities and projects, the Minimuseu Firmeza was gestated and developed always surrounded by resistance and affection, in addition to the field's own disputes that demarcate power relations. It also presents the couple's contribution to the history and development of the field of heritage and art history in Ceará.